2009
DOI: 10.1007/s12376-009-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation’s Return: Anti-aging and Re-masculinization in Biomedical Discourse on the ‘Aging Male’

Abstract: Since the late 1990s, a constellation of professional associations, journals and health promotion materials has emerged that has constructed the 'aging male' as a medical problem. Central to this construction has been a revival of a hormonal model of the male body in which anti-aging is linked to the restoration of masculinity. In this paper I revisit the association of aging and demasculinization that animated the rejuvenation movement of the early 20th century, and contrast this with the initial mainstream m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
(35 reference statements)
0
9
0
Order By: Relevance
“… [34] Indeed, in our study we found that rates of topical TRT use have increased consistently since its introduction in 2005 as compared to rates of oral and injectable TRT use, which have remained relatively stable since 2006. Finally, publications related to testosterone use are given considerable exposure in the lay and medical press, which further drives medicalization of aging, drug campaigns and development of new products [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%
“… [34] Indeed, in our study we found that rates of topical TRT use have increased consistently since its introduction in 2005 as compared to rates of oral and injectable TRT use, which have remained relatively stable since 2006. Finally, publications related to testosterone use are given considerable exposure in the lay and medical press, which further drives medicalization of aging, drug campaigns and development of new products [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%
“…As Tiefer (:287) notes, the triumph of oral erectile medications “succeeded so thoroughly in rationalizing the idea of sexual correction and enhancement through pills that it only seems fair that such a product be made available to women,” launching the “hunt for pink Viagra” (Wyllie ). There has also been renewed interest in identifying a hormonal (and thus pharmaceutically correctable) basis for symptoms of sexual decline linked to the “male menopause” or “andropause” (Marshall ; Watkins ).…”
Section: The Medicalization Of Sexualitymentioning
confidence: 99%
“…It thus aligns with other ways of recuperating successful aging futures through, for example, anti-aging culture's promotion of sexuo-pharmaceuticals and other 6 There is also clearly a reassertion of patriarchal linearity here, although this is beyond the scope of the present paper. biomedical means of restoring happy futures [13,50,51]. As Emily Wentzell [52] cautions, expansion of biomedical control over non-normative bodies risks deflecting attention away from the social interventions that could create the conditions for a diversity of more livable futures.…”
Section: Repairing the Future?mentioning
confidence: 99%